Risk factors for further sick leave among Japanese workers returning to work after an episode of major depressive disorder: a prospective follow-up study over 1 year - Hikaru Hori; Asuka Katsuki; Kiyokazu Atake; Reiji Yoshimura; Jun Nakamura; Bernhard T Baune (BMJ Open)
Objectives We aimed to investigate the risk factors for further sick leave episodes among Japanese workers returning to work after time off with a major depressive disorder.Design A prospective study with 1 year of follow-up.Participants We recruited 103 workers who had returned to work after taking sick leave with a major depressive disorder. Adjusted HRs with 95% CIs were calculated using Cox proportional hazard models to examine the risk of further sick leave.Results In the adjusted analysis, we show that Social Adaptation Self-evaluation Scale scores (HR 0.95; p=0.019), 3-back correct response rate (N-back test) (HR 0.97; p<0.001) and benzodiazepine dosage (diazepam equivalent) (HR1.07; p=0.014) were associated with further episodes of sick leave.Conclusions Poorer social and cognitive functioning, together with higher diazepam dosages, were associated with an increased likelihood of additional sick leave.